Heralding a New Era for Higher Education Institutes: Moving Towards Implementation of National Education Policy 2020: A Pharmacy Undergraduate Program Perspective - Upadhya, Archana; Saraf, Madhusudan Natvarlal (Indian Journal of Pharmaceutical Education and Research, 2025)
The National Education Policy (NEP) 2020 has been drafted to bring about a paradigm shift in the prevailing system of education at the school and higher educational levels (Undergraduate and Post graduate Degree programs). The NEP 2020 policy has been designed to ensure that education is reachable to all learners who can avail it at their own pace and according to their needs. Taking academic breaks which was previously unheard of in the Indian education scenario has been made plausible via the NEP 2020. Weightage to the courses taken by the student online and offline is given in the form of credits and each student is recommended to maintain an academic bank of credits account. This article gives an overview of the NEP 2020 policy with respect to higher education with special emphasis to implementation of the undergraduate programs. Recommendation for course structure (as per NEP 2020) for the undergraduate Pharmacy program has been described in detail in comparison with the existing course structure.
Keywords: Pharmacy Course Structure; Pharmacy Council of India; National Education Policy; 2020; University Grants Commission; Credits